2020
DOI: 10.1021/acs.est.0c01080
|View full text |Cite
|
Sign up to set email alerts
|

Novel Disinfection Byproducts Formed from the Pharmaceutical Gemfibrozil Are Bioaccumulative and Elicit Increased Toxicity Relative to the Parent Compound in Marine Polychaetes (Neanthes arenaceodentata)

Abstract: Formation of halogenated disinfection byproducts (DBPs) from pharmaceutically active compounds has been observed in water supply systems following wastewater chlorination. Although research has been limited thus far, several studies have shown that halogenated DBPs may elicit increased toxicity compared to their parent compounds. For example, the lipid regulator gemfibrozil has been shown to form chlorogemfibrozil (Cl-gemfibrozil) and bromogemfibrozil (Br-gemfibrozil) following chlorination, which are more pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…For aquatic organisms, increased bioaccumulation of contaminants is often attributed to a compound’s hydrophobicity, as bioaccumulation is driven by lipids in an organism and is positively related to hydrophobicity or log K ow for neutral compounds. ,,,, Increased bioaccumulation after methylation was previously observed for diclofenac in aquatic invertebrates. Bioaccumulation of methylated diclofenac was found to be 25–110-fold that of diclofenac in H.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…For aquatic organisms, increased bioaccumulation of contaminants is often attributed to a compound’s hydrophobicity, as bioaccumulation is driven by lipids in an organism and is positively related to hydrophobicity or log K ow for neutral compounds. ,,,, Increased bioaccumulation after methylation was previously observed for diclofenac in aquatic invertebrates. Bioaccumulation of methylated diclofenac was found to be 25–110-fold that of diclofenac in H.…”
Section: Resultsmentioning
confidence: 96%
“…The consensus QSAR method in the U.S. EPA’s Toxicity Estimation Software Tool (T.E.S.T., version 5.1.2) was used to predict the acute toxicity of the target compounds in D. magna . The BCF and the biotransformation half-life values of test compounds were obtained by using the BCFBAF model in the U.S. EPA’s EPI Suite software (version 4.11).…”
Section: Methodsmentioning
confidence: 99%
“…The generation of more hydrophobic transformation products was also shown to enhance the disruption of key receptors in relation to their parent compounds, such as triclosan and bisphenol S. 50 As the AR antagonists currently in use are halogenated, 24,51 the enhanced AR-disrupting effect of chlorinated BP-1 products may be directly related to the chlorine moiety. Similarly, gemfibrozil was transformed into Cl-gemfibrozil and Brgemfibrozil following disinfection, 15,52 resulting in higher antiandrogenic activity in male Japanese medakas as well as increased bioaccumulation and acute toxicity in Neanthes arenaceodentata. Because antagonism to AR during the critical stage of mammary gland development was associated with an irreversible demasculinizing consequence and aberrant development of the male reproductive tract, 53,54 the enhanced antiandrogenic activity of BP-1 introduced by chlorination may trigger a risk for deteriorated health.…”
Section: Resultsmentioning
confidence: 99%
“…The chlorination of chemicals has frequently been observed during the disinfection process. , Previous studies have shown that free chlorine at dosages up to 200 μM can transform benzophenones into various chlorinated products, , which was associated with increased acute toxicity to luminescent bacteria, and higher genotoxicity. The recommended residual chlorine level for swimming pools is 0.2–1.0 mg/L for safe use; however, whether this low level of residual chlorine could trigger the natural occurrence of BP-1 chlorination remains unknown. Additionally, little is known concerning the joint toxicity of a potentially large number of chlorinated byproducts with varying toxicities .…”
Section: Introductionmentioning
confidence: 99%
“…Next year, they reported DMSO-catalyzed chlorination of bioactive molecules using NCS, demonstrating the compatibility of this mild reaction condition with numerous natural products and drugs ( Scheme 8 c) 136 . Notably, the chlorination of gemfibrozil, a lipid-lowering drug, was shown to decrease its solubility in water 137 , and potentially enhance its antiandrogen activity 138 . In 2021, they also developed alternative system in which DMSO was replaced by nitroxides appeared and expanded the substrate scope of the past work 139 .…”
Section: Halogenation Of Bioactive Compoundsmentioning
confidence: 99%